Studi Penetrasi Applikasi Media Sosial Instagram Sebagai Media Pemasaran Digital Pada UMKM - Budiman, Jovito Bryant; Deu, Indasari (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Digital marketing is one of the important elements in the product sales strategy in the digital era. Developing technology and increasing internet penetration allow MSMEs to reach a larger audience. An effective digital marketing strategy can increase product visibility, attract potential customers, and increase sales. Widely used social media such as Instagram is very effective as a means of marketing communication, building brand awareness and engagement with customers, as well as expanding business networks through attractive and interactive content. This research applies the Systematic Literature Review method. Based on the results of the systematic literature review, the authors found 30 selected articles for descriptive analysis. By examining the research that has been done previously on the influence of Instagram social media on the world of digital marketing, the author will conclude how much impact Instagram social media has on the current digital marketing world.